2019
DOI: 10.4103/apjon.apjon_14_19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Internal Validity Threats to Phase III Clinical Trials for Chemotherapy-Induced Peripheral Neuropathy Management: A Systematic Review

Abstract: Objective: The recent American Society of Clinical Oncology (ASCO) Clinical Guidelines for chemotherapy-induced peripheral neuropathy (CIPN) management (48 Phase III trials reviewed) only recommend duloxetine. However, before concluding that a CIPN intervention is ineffective, scientists and clinicians should consider the risk of Type II error in Phase III studies. The purpose of this systematic review was to characterize internal threats to validity in Phase III CIPN management trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Both studies used the physician-graded Common Terminology Criteria for Adverse Events (CTCAE) to assess the primary outcome. A growing body of literature provides evidence of the CTCAE’s psychometric limitations (Alberti et al, 2014; Griffith et al, 2010; Park et al, 2019; Postma et al, 1998), and these limitations have compromised the internal validity of most CIPN intervention trials that have been conducted over the past 30 years (Gewandter et al, 2018; Hershman et al, 2014; Lee et al, 2019; Loprinzi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies used the physician-graded Common Terminology Criteria for Adverse Events (CTCAE) to assess the primary outcome. A growing body of literature provides evidence of the CTCAE’s psychometric limitations (Alberti et al, 2014; Griffith et al, 2010; Park et al, 2019; Postma et al, 1998), and these limitations have compromised the internal validity of most CIPN intervention trials that have been conducted over the past 30 years (Gewandter et al, 2018; Hershman et al, 2014; Lee et al, 2019; Loprinzi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of evidence surrounding the underlying mechanisms of neuropathy, a limitation to determining new treatments for CIPN prevention is the overall poor study quality of previously conducted randomized clinical trials [7,8]. For example, Lee et al (2019) conducted a systematic review to characterize internal threats to validity of Phase III CIPN prevention or management trials between 1990 and 2018. The authors reported that 16/17 (94%) Phase III CIPN prevention clinical trials had two or more internal threats to validity (e.g., confounding variables, lack of reliable measurement or statistical validity) [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee et al (2019) conducted a systematic review to characterize internal threats to validity of Phase III CIPN prevention or management trials between 1990 and 2018. The authors reported that 16/17 (94%) Phase III CIPN prevention clinical trials had two or more internal threats to validity (e.g., confounding variables, lack of reliable measurement or statistical validity) [9]. To improve CIPN clinical trial design, the Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks Consortium on Clinical Endpoints and Procedures for Peripheral Neuropathy Trials released several recommendations for CIPN clinical trial design [7,8].…”
Section: Introductionmentioning
confidence: 99%